Enhancing Infrastructure through the Effectiveness of Village Funds - Zahran, Evan Dwi; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study employs a descriptive approach and purposive sampling to investigate the effectiveness of village funds in Bluru Kidul Village, Sidoarjo District, Indonesia, utilizing Martani and Lubis' Effectiveness Theory. Despite positive strides in infrastructure development, challenges persist, particularly in the delayed repair of damaged roads leading to flood-related disruptions in community mobility. The village head plays a crucial role in fund management, and this research aims to shed light on the existing constraints. By exploring the gap between expectations and reality, our findings contribute to a better understanding of the complexities surrounding village fund utilization Highlight : Challenges in Road Maintenance: Despite successful infrastructure development, delayed repairs of damaged roads in Bluru Kidul Village contribute to flood-related disruptions, impacting community mobility. Village Head's Role: Effective village fund management hinges on the leadership of the village head, emphasizing the pivotal role they play in ensuring the funds align with community needs. Research Contribution: This study, utilizing Martani and Lubis' Effectiveness Theory, contributes valuable insights into the complexities surrounding village fund utilization, shedding light on the gap between expectations and the actual welfare and equity improvements in Bluru Kidul Village, Sidoarjo Keywords: Village Funds, Infrastructure Development, Fund Management, Sidoarjo, Effectiveness Theory